Impact of urbanisation and agriculture on the diet of fruit bats - Lim, Voon Ching; Clare, Elizabeth L.; Littlefair, Joanne E.; Ramli, Rosli; Bhassu, Subha; Wilson, John-James (Springer Verlag, 2018)
The expansion of cities and agricultural plantations have unpredictable impacts on biodiversity and ecosystem services. Yet some species are capable of tolerating anthropogenic impacts and continue to provide ecological services in highly disturbed landscapes. The objective of this study was to use DNA barcoding to identify digested plant materials and seeds in the faeces of frugivorous bats (Cynopterus brachyotis) and investigate whether (1) C. brachyotis in urban and agricultural areas exploit cultivated and exotic plants as a novel food resource and as a consequence, potentially facilitate the invasion of cultivated and exotic plants, or whether (2) C. brachyotis exploit native plants and as a consequence, potentially promote forest regeneration. A native species, Ficus fistulosa, was the most frequently detected plant and the seeds were found in bat faeces from all sampling sites suggesting the potential of fruit bats in dispersing seeds. However, we also detected several exotic plants in the faeces of C. brachyotis which suggests that the fruit bats exploit novel food resources at all sites. We recorded a diverse diet of C. brachyotis at an oil palm plantation which indicated that the fruit bats are not predominantly feeding on oil palm fruits. By using DNA barcoding, we detected plants that have not been reported in previous studies of the diet of C. brachyotis, although we could not identify which part of the plant was being consumed by the fruit bats. Given the varied diet of C. brachyotis, the potential of this bat to adapt to changing landscapes is high and they are likely dispersing seeds of native pioneer plants (Ficus).